ANALISIS BEBAN KERJA MENTAL, BEBAN KERJA FISIK DAN STRES KERJA PADA PEKERJA DI TAMAN PENITIPAN ANAK MENTARI - Ari Pradina; Ekawati Ekawati; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2018)
Daycare is one of the non-formal education for early childhood. One of the main components of daycare is caregivers. Caregivers are at risk of experiencing work stress due to task demands. Caregivers must always be vigilant in supervision and required to be active when working. Therefore, researchers conduct research to find out what factors can increase workload so that it can cause work stress. The purpose of this study is to analyze mental workload, physical workload, and work stress on workers in the Mentari Daycare. The design of research is descriptive qualitative. Research subjects were 3 caregivers as the main informant and 1 owner as triangulation informant. Data collection method is divided into 2 stages: measurement with questionnaire and observation followed by in-depth interviews. Mental workload was measured using NASA-TLX, physical workload was measured using SNI Workloads Based on Calorie Requirement Levels According to Energy Expenditures, and work stress was measured using GHQ-12. Furthermore, SOP observations and in-depth interviews were carried out. The measurement results obtained that 1 person experienced high stress and 2 people experienced low stress. One person who experiences high stress gets a high mental workload and light physical workload. Two people who experience low stress get moderate mental workload and light physical workload. While the factors examined such as situation, training, practice, skills, boredom, permissible performance tolerance, and completion time led to an increase in workload coupled with individual characteristics so as to trigger work stress.